A low profile dual band resonant cavity antenna. Issue 2 (1st November 2016) - Vaid, Swati; Mittal, Ashok
Abstract: A low profile dual band resonant cavity antenna that incorporates double sided partially reflective surface (PRS) with complementary layers is presented here. The PRS is formed by printing periodic array of complementary metallic square loops on the opposite sides of the dielectric material. The PRS has been used as a superstrate, placed above the radiating microstrip patch. This PRS acts as a dual band matching section between the microstrip patch and free space, hence resulting in dual resonance. The proposed structure has been analyzed using equivalent circuit model. Parametric analysis of the sensitive structural parameters has also been discussed. To validate the design, the simulation analysis and experimental results obtained from a prototype operating at 8.9 and 9.4 GHz are presented. The measured gain at the two frequencies is 10.2 and 8.5 dBi, respectively. The overall size of the antenna is 1.78λ × 1.78λ × 0.09 λ with λ corresponding to 8.9 GHz.